O papel do supervisor pedagógico - Franz, Ana Maria da Silva (2016)
Submitted by Kelly Ayala (kelly.ayala@fgv.br) on 2016-06-07T19:45:21Z No. of bitstreams: 1 000055313.pdf: 11177023 bytes, checksum: 5c9ec611750e7dca9947863b33ff4adf (MD5) === Made available in DSpace on 2016-06-07T19:46:20Z (GMT). No. of bitstreams: 1 000055313.pdf: 11177023 bytes, checksum: 5c9ec611750e7dca9947863b33ff4adf (MD5) Previous issue date: 1990-12-12 === The present study searches for the actual role of the Pedagogical Supervisor in the Context of Brazilian Education. The objective of this work is to investigate the historical origin of Educational School Supervision in Brazil and in particular in the State of Minas Gerais, analising the relationship between the Pedagogical Supervisor and School Education. It also examines the effects of Educational Supervision in the brazilian School system its beginning. From The study focuses on the educational background of the Pedagogical Supervisor taking into account the theoretical basis used in the Pedagogical Courses with the objective of explaining, from the legal standpoint, its appearance, its specific qualifications and historical evolution. This work researches the political influence of Pedagogical Supervisors through a systematization of its practice, stressing the teacher's corporative movement which is proposing reforms in the current Educational System. This study concludes with an analysis of the educational movement of the 70's and 80's speculating its influence on the decade that follows. === O presente estudo busca o real Papel do Supervisor Pedagógico no Contexto Educacional Brasileiro. Objetiva investigar a origem histórica da Supervisão Escolar no Brasil e no Estado de Minas Gerais, analisando a relação Supervisor Pedagógico - Educação Escolar e as conseqüências da sua inclusão na Escola Pública Brasileira. Focaliza o processo de formação do Supervisor Pedagógico considerando o tipo de linha teórica presente nos Cursos de Pedagogia, buscando retomar, historicamente, na sua evolução, o seu surgimento e as habilitações específicas nele implícitas, a partir do aspecto legal. Busca a dimensão política da categoria dos Supervisores Pedagógicos, através da sistematização de sua prática, em processo, destacando-se o movimento corporativo dos educadores propondo reformas no atual Sistema Educacional. Conclui analisando o movimento educacional dos anos 70/80, levantando questões sobre a influência desse movimento na década que se inicia.